DUNIA MAGIS DALAM CERPEN LEAK PEMOROAN KARYA I WAYAN SADHA - I Wayan Juliana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
of the occult not only lived in the past but penetrated freely until Era 4.0. Although the development of the world has advanced in such a way as with the sophistication of its technology, the belief in supernatural and magical things cannot be erased. The magical world has its own charms and problems in the lives of Balinese people. Undeniably, the attractiveness often invites the attention of the author in welcoming and recording the phenomenon into literary works. In this paper examines modern Balinese literary works in the form of short stories. The short stories studied were taken from a collection of Leak Pemoroan stories written by I Wayan Sadha. This study examines three short stories in a collection of Pemoroan Leak short stories entitled Jeg Pragat Ka Balian, Pemoroan Leak and Walik Sumpah. The focus of the discussion in this paper is to raise the magical aspects contained in the three short stories that have been mentioned. The magical aspects to be discussed are the Pangiwa aspect and the Panengen aspect contained in the short story.Keywords: Magic, Pangiwa, Panengen, Short Story, modern Balinese literature